2013
DOI: 10.1371/journal.pone.0084561
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Ecosystem Response to Timber Harvesting for the Purpose of Restoring Aspen

Abstract: The removal of conifers through commercial timber harvesting has been successful in restoring aspen, however many aspen stands are located near streams, and there are concerns about potential aquatic ecosystem impairment. We examined the effects of management-scale conifer removal from aspen stands located adjacent to streams on water quality, solar radiation, canopy cover, temperature, aquatic macroinvertebrates, and soil moisture. This 8-year study (2003–2010) involved two projects located in Lassen National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
2
1
0
Order By: Relevance
“…The average age for the harvested forests in this study followed the trend west > south > north (Tables 2–5), and studies have shown the importance of age of forest materials on decomposition rates (Troendle et al, 2010; Jones et al, 2013). Mature conifer forests have also been reported to use more water than mature aspen forests, leading to less nutrient export (Jones et al, 2013).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The average age for the harvested forests in this study followed the trend west > south > north (Tables 2–5), and studies have shown the importance of age of forest materials on decomposition rates (Troendle et al, 2010; Jones et al, 2013). Mature conifer forests have also been reported to use more water than mature aspen forests, leading to less nutrient export (Jones et al, 2013).…”
Section: Resultssupporting
confidence: 56%
“…The average age for the harvested forests in this study followed the trend west > south > north (Tables 2-5), and studies have shown the importance of age of forest materials on decomposition rates (Troendle et al, 2010;Jones et al, 2013). Mature conifer forests have also been reported to use more water than mature aspen forests, leading to less nutrient export ( Jones et al, 2013). Stream flow response was also reported to be affected by species composition and the percentage change in vegetation density in the western region (Troendle et al, 2010), and in the eastern coastal plain ( Jayakaran et al, 2014), with a potential to affect nutrient and sediment exports.…”
Section: Effects Of Plant Species Distributionsupporting
confidence: 57%
“…For example, the Washington State Department of Natural Resources outlines riparian management strategies to restore conifer dominated riparian areas (Bigley and Deisenhofer, 2006). Additional studies in Lassen National Forest seek to restore aspen stands for habitat and ecosystem services (Jones et al, 2013). Furthermore, there has been documented success at releasing suppressed conifers in riparian areas using patch cutting and thinning in parts of Oregon (Emmingham et al, 2000;Maas-Hebner et al, 2005).…”
Section: Riparian Vegetation Conversionmentioning
confidence: 99%